The Role of Social Capital in the Relationship between Psychological Capital and Leader Member Exchange on Organizational Citizenship Behavior - Kukuh Adi Sri Satyanto; Euis Soliha (Universitas Pamulang, 2022)
This study aims to determine the mediating effect of social capital variables on psychological capital and leader-member exchange on organizational citizenship behavior with a study on employees of PT Pos Indonesia (PERSERO). The sample of this research is all employees of PT Pos Indonesia (Persero) Semarang Post Office Ungaran Area who have a working period of more than one year. The analysis technique uses statistical analysis with regression testing, validity testing, reliability testing, determination and hypothesis testing. The results of this study that psychological capital and LMX have a significant effect on OCB. The results of this study that psychological capital, LMX and social capital have a significant effect on OCB. Isocial capital mediates the effect of imodal psychology on Organizational Citizenship Behavior. Isocial capital mediates the effect of Leader-member exchange on Organizational Citizenship Behavior.